Analysis of Sex Differential Immunity and its Impacts on Health: A Comprehensive Review - Mallick, Diptarup (International Journal of Scientific Research in Biological Sciences, 2024)
Sex as a bio-variable affects both male and female immunity. Immunologically and phylogenetically both males and females are separated in terms of their innate and adaptive immunity and responses to self and non self antigens also and there are several influencing factors involved. Some sex differences in immune responses persist life long, while others become visible only after adolescence and before old age , indicating many immune regulatory genes( those on sex chromosomes) and sex hormones are equally engaged. There are four different life stages viz. fetal stage, childhood, adolescence and aging stage are characterized by sex differential levels of immunocytes, sex hormones and immune responsiveness . In addition ,microbiomes are influenced by early environmental exposures that also leads to sex differential immune responses. As well as micronutrient supplementations provide female-biased immunity. Henceforth, these sex differential immunity leads to variations in the frequency of some immunosuppressive diseases such as diseases caused by autoimmunity and malignant cancers, proneness to communicable diseases. Similarly differential vaccine efficiency are also seen in men and women and these differences affect their overall survival.